Assessment of the Implementation of Nigeria’s Freedom of Information Act 2011 and Its Effectiveness in Katsina State - Ibrahim Abdulkadir; Timothy Ekeledirichukwu Onyejelem; Carol Dixon Odoyi; Chidinma N. Ejekwu (Polit Journal Scientific Journal of Politics, 2025)
The freedom of the press is an essential ingredient for democracy; the law governing the press in democratic countries are those which only seek to protect the fundamental rights of individuals and ensure the maintenance of peace and order. The objectives of the study were to review provisions of the freedom of information Act and to find out whether journalists in Katsina State use the Act. The study is situated within the theoretical framework of Libertarian Theory. Document analysis was used as the study method. The three criteria for accessing the quality of the evidence available from documentary sources as were authenticity, credibility and representativeness. Based on the document analysis, access sections give an insight that the freedom of information Act 2011 is under-utilized by journalists in Katsina State. The documentary analysis reveals that only sections 1(b) and 3 provides freedom to access public information, 10 sections are meant to deny the public information. The study discovered that ignorance among some journalist and managers of public documents are also affecting the workability of the act in Katsina State. The documentary analysis revealed that the act only provides access in 2 sections while about 10 sections and some clauses are meant to deny access to public information, the finding equally suggests that ignorance among some journalists and managers of public documents are factors affecting the workability of the act of Katsina State.